The Abstraction Principle and the Separation Principle in German Law - Sadowski, Kornel (Europejskie Stowarzyszenie Studentów Prawa ELSA Poznań, 2014)
The aim of the study is to evaluate the selected principles applied in German law system – the abstraction principle and the separation principle. Presenting the proposed subject the author focus on the obligatory and dispositive legal acts and practical dimensions of the functioning of the selected principles.
The Abstraction Principle and the Separation Principle in German Law
Keywords: abstraction principle; separation principle; German law system